2021
DOI: 10.5194/aab-64-365-2021
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of indigenous Lao pigs reared by small-scale farmers in northern provinces of Laos

Abstract: Abstract. Indigenous pigs are essential domestic animals for rural life and meat supply in Laos, especially for ethnic people in remote areas. Northern provinces have the most numerous indigenous pig populations, i.e. covering 84 % of the total pig population. This study was conducted in northern Laos, where 164 pig-raising households, 325 sows and 1246 piglets were included. The study aimed to observe the general trend of change in indigenous pig utilization and the altered reproductive performance regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…However, some reports indicated that Moo Lath gilts could reach puberty at about 150−180 days, with a body weight ranging from 30−39 kg (Wilson, 2007;Keonouchanh et al, 2011). On the other hand, small-scale farmers in Northern Laos reported that their Moo Lath reached puberty between 120−150 days old (Xayalath et al, 2021). The average litter birth weight of Moo Lath or other Lao indigenous piglets is typically between 0.5 and 0.7 kg (Phengvilaysouk et al, 2018;Manivanh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, some reports indicated that Moo Lath gilts could reach puberty at about 150−180 days, with a body weight ranging from 30−39 kg (Wilson, 2007;Keonouchanh et al, 2011). On the other hand, small-scale farmers in Northern Laos reported that their Moo Lath reached puberty between 120−150 days old (Xayalath et al, 2021). The average litter birth weight of Moo Lath or other Lao indigenous piglets is typically between 0.5 and 0.7 kg (Phengvilaysouk et al, 2018;Manivanh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%